Factors associated with perioperative mortality in children and adolescents operated for tetralogy of Fallot: A sub‐Saharan experience. Issue 12 (10th October 2019) - Tefera, Endale; Gedlu, Etsegenet; Nega, Berhanu; Tadesse, Birkneh T.; Chanie, Yilkal; Dawoud, Ali; Moges, Fekadesilassie H.; Bezabih, Abebe; Moges, Tamirat; Centella, Tomasa; Marianeschi, Stefano; Coca, Ana; et al.
Abstract: Background: Patients with tetralogy of Fallot are now surviving to adulthood with timely surgical intervention. However, many patients in low‐income countries have no access to surgical intervention. This paper reports the surgical access and perioperative mortality in a sub‐Saharan center that was mainly dependent on visiting teams. Methods: We reviewed records of patients operated from January 2009 to December 2014. We examined perioperative outcomes, primarily focusing on factors associated with perioperative mortality. Results: During this period, 62 patients underwent surgery. Fifty‐seven (91.9%) underwent primary repair, while 5 (6.5%) underwent palliative shunt surgery. Of the five patients with shunt surgery, four ultimately underwent total repair. Eight (12.9%) patients died during the perioperative period. Factors associated with perioperative mortality include repeated preoperative phlebotomy procedures ( P  < .001), repeated runs and long cardiopulmonary bypass time ( P  < .001), and aortic cross‐clamp time ( P  < .001), narrow pulmonary artery (PA) valve annulus diameter ( P  = .022), narrow distal main PA diameter ( P  = .039), narrow left branch PA diameter ( P  = .049), and narrow right PA diameter ( P  = .039). Of these factors, cardiopulmonary bypass time/aortic cross‐clamp time and pulmonary valve annulus diameter less than three SD were independently associated with perioperative mortality. Conclusion: In this series of consecutive patients operated by a variety of humanitarian surgical teams, cardiopulmonary bypass time/aortic cross‐clamp time, and pulmonary valve annulus diameter less than three SD were independently associated with perioperative mortality risk. As some of these factors are modifiable, we suggest that they should be considered during patient selection and at the time of surgical intervention.